Fenomena al-Qur’an: Tafsir Integral Malik Bennabi - Usman Syihab Husnan (Refleksi: Jurnal Kajian Agama dan Filsafat, 2004)
This article delves into the pattern of interpretation or approach taken by Malik Bennabi in understanding the Qur'an. Malik Bennabi's approach to revelation is integral in nature. By examining Malik's work, "The Phenomenon of the Qur'an," Usman draws the conclusion that Malik Bennabi successfully provided a mature response to the challenges posed by Western philosophy and thought in viewing the Qur'an. By positioning the Qur'anic revelation as an objective phenomenon that transcends all historical contexts and various forms of socio-cultural backgrounds, Malik Bennabi was able to address Orientalists who denied and sought to sow doubts about the truth of the Qur'an as the revelation of God. Malik Bennabi responded to Margelyouth (an English Orientalist) and his colleagues who regarded the Qur'an as a product of Prophet Muhammad or a copy of the Torah and the Gospel, or who claimed that the Qur'an was influenced by both of these covenant books. Through his work, Malik Bennabi also indirectly rejected the philology of Christoph Luxenberg (a German Orientalist) who came much later, accusing the Qur'an of being originally written in Aramaic rather than Arabic.